Model Kolaboratif Interaktif Readaloud untuk Mendukung Literasi Membaca di Sekolah Dasar - Istikhoroh Nurzaman (Jurnal Elementaria Edukasia, 2023)
This study is based on the urgency in understanding of the text presented. The aim of this research is to produce a collaborative interactive read aloud learning model as an effort to create understanding of the text. The model applied includes: 1) Designing; 2) Forming; 3) Facilitating; 4) Evaluating. This research was carried out by adapting McKenny & Reeves through the stages of EDR development research procedures which include: 1) Problem Identification; 2)Design and Construction; 3) Evaluation and Reflection. Data collection techniques were carried out by interviews and observation. The research subjects involved teachers and students at SDN Karangsambung, Tasikmalaya City. The conclusions of this research indicate that the collaborative interactive read aloud model can be implemented in reading learning to support elementary school students' reading comprehension